Training simulator for special physical fitness and technical skills excellence in sprint sport - Mirzoev, O. M.; Mukhin, O. A. (Theory and Practice of Physical Culture, 2017)
The article presents a new technology to improve and maintain sprint skills and sport-specific physical qualities and abilities in sprinters running 60-400m distances. The study data may also be beneficial for the highly-skilled athletes at their excellence training and top mastery stages when the progress is not that high as at the beginner stages of the athletic careers. The proposed training simulator is designed to create facilitating conditions for the speed and speed-strength qualities, special endurance and the most efficient running techniques being maintained and improved in sprinters. The training simulator may be applied to solve a few training tasks at a time to attain combined positive effects on physical fitness and technical mastery for competitive progress.